The Promising Role of Microbial Pigments in Therapeutic Interventions from Antimicrobial to Anticancer Applications (International Journal of Food and Nutritional Sciences, 2022)
The antibacterial, anticancer, cytotoxic, and exceptional antioxidant characteristics of the bacterial pigments demonstrate their therapeutic nature. Because of the significance of bacterial pigments, a thorough analysis of the literature about the medicinal and industrial applications of bacterial pigments was deemed necessary. UV-visible spectroscopy was used to characterize the pigment; the absorption spectra span from 220 to 250 nm. After FTIR examination, the spectrum for strain BJZ10 revealed functional groups associated with alcohols, esters, sulfate, alkanes, and alkyls. (Gram-positive) Bacillus cereus and (Gram-negative) Escherichia coli were used to assess the pigments' antibacterial action, and significant results were compared. This investigation uncovered the brown pigment, renowned for its possible antibacterial properties, produced by Streptomyces sp. strain BJZ10. We will talk about in this essay. Microbial Pigments' Potential Use in Therapeutic Interventions: From Antimicrobial to Anticancer Applications.